98 Socioeconomic deprivation score improves prediction of af recurrence and re-admission post AF ablation. (4th June 2021) - Lau, Yee Cheng; Sim, Krystalina Yih Tyng; Cimpeanu, Oana; Marshall, Gillian E; Padfield, Gareth J; Wright, Gary A; Dobson, Richard; Connelly, Derek T
Abstract : Background: Atrial fibrillation (AF) recurrence post catheter ablation can occur in up to 50% within 12 months of treatment. Previously, several novel scoring systems have been suggested, inclusive of CHADS2VASc, R2CHADS2, CHADS2 and APPLE score. Nevertheless, prediction of AF recurrence and subsequent readmission remains difficult. Methods and Results: 383 consecutive patients attended the Golden Jubilee National Hospital, Glasgow, to undertake cryoablation for AF. Average age 58 (± 13), 64% male, BMI 29 (± 4.7), 60% paroxysmal AF. Degrees of socioeconomic deprivation as per Scottish Index of Multiple Deprivations (SIMD) were recorded in deciles. Patients were followed up to at least 12 months post procedure. After initial 3-month blanking period, symptomatic recurrence of documented AF (not SVT/Atrial tachycardia/Flutter) requiring admission to hospital were observed in 86 patients (22.5%). Individual CHADS2VASc Score, R2CHADS2 (R for renal dysfunction), APPLE Score(one point for Age >65 years, Persistent AF, imPaired eGFR (<60 ml/min/1.73m2), Left atrial diameter ≥43 mm, left ventricular Ejection fraction <50%) were recorded and compared to Scottish Index of Multiple Deprivations (SIMD) using statistical methods to assess for AUC as per ROC Curve.In the current cohort of patients, previous scoring systems CHA2DS2-VASc score (AUC 0.5337 (95% CI 0.4336 – 0.6338, p = 0.287), R2CHADS2 score (AUC 0.5202 (95% CI 0.4201 – 0.6203, p = 0.874) and APPLE score (AUC0.5523 (95% CI 0.4522 – 0.524, p = 0.049)) demonstrated lower predictive values, while SIMD demonstrating better prediction of AF recurrence requiring readmission (AUC 0.6145 (95% CI 0.5144 - 0.7146, p=0.001)). SIMD also demonstrated to better predicts recurrence of subjective AF recurrence (AUC 0.6096, 0.5095 - 0.7097, p <0.001). Addition of SIMD into CHADS2VASc, R2CHADS2 or APPLE Score through various modeling did not improve predictive value of AF recurrence or readmission. Conclusion: Scottish Index of Multiple Deprivation is superior to the CHA2DS2-VASc, R2CHADS2 and APPLE scores for prediction of readmission and recurrence of symptomatic AF after AF cryoablation. Conflict of Interest: No